New Electromagnetic Force-Displacement Sensor - Amine Benabdellah; Zakarya Abbassi; Abdelrhani Nakheli (Bulletin of Electrical Engineering and Informatics, 2016)
A new electromagnetic force-displacement sensor is presented. Its operating principle is based on the fundamental laws of electromagnetism (Faraday-Lenz law) and the mechanical properties of a spring. The active elements are two coils made by a wire of 60 µm in diameter. Using different wire diameters or different number of wire turns in the coil modify the intensity of the magnetic field and the sensor response. The average accuracy of the sensor is about ∆d=1µm, and as a force sensor is about ∆F=1µN. This sensor could be successfully used for the manufacture of several measuring instruments.